2013
DOI: 10.1590/0103-6440201302352
|View full text |Cite
|
Sign up to set email alerts
|

Predisposing Factors for Traumatic Dental Injury in Primary Teeth and Seeking of Post-trauma Care

Abstract: The aim of the present study was to investigate predisposing factors for traumatic dental injury (TDI) in the primary dentition and seeking of dental care after the occurrence of TDI. A randomized population-based cross-sectional study was carried out with 814 children aged 3 to 5 years enrolled at public and private preschools in the city of Campina Grande, PB, Brazil. Parents were asked to fill out a questionnaire on demographic data and the child's history of TDI. TDI was evaluated by clinical examinations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 16 publications
1
56
0
11
Order By: Relevance
“…After the screening procedure, 26 papers remained. Of these, nine papers were excluded for various reasons, thus leaving seventeen primary studies for the meta‐analysis. The paper of Peerhentupa et al.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the screening procedure, 26 papers remained. Of these, nine papers were excluded for various reasons, thus leaving seventeen primary studies for the meta‐analysis. The paper of Peerhentupa et al.…”
Section: Resultsmentioning
confidence: 99%
“…, and self‐reported TDI (Table ). The majority of studies included overweight and obese subjects in the exposed group , three studies included obese subjects only , while three studies merged obese/overweight subjects with normal‐weight subjects who were close to the overweight threshold .…”
Section: Resultsmentioning
confidence: 99%
“…There is a general consensus that older children have a greater likelihood of exhibiting TDI . The few studies that did not report significant differences among ages examined samples with a very small age range . However, rather than demonstrating that an older age represents greater risk, this information demonstrates that TDI is a cumulative outcome.…”
Section: Factors Associated With Tdi In the Primary Dentitionmentioning
confidence: 95%
“…A recent systematic review including children, adolescents, and adults concluded that accentuated overjet accounts for 22% of TDIs worldwide . Indeed, accentuated overjet is the most commonly identified risk/associated factor in the primary dentition (). Studies also report that inadequate lip seal and open bite are risk factors, as children with these conditions are more exposed to fractures and displacements in cases of falls and collisions .…”
Section: Factors Associated With Tdi In the Primary Dentitionmentioning
confidence: 99%
“…Recent studies carried out in Brazil have shown high prevalence rates of adverse oral conditions, especially in areas with social inequalities, such as the area in which the present study was conducted [10-12]. …”
Section: Introductionmentioning
confidence: 99%